A Study in Water Balance and Climatic Characteristics of Varanasi - Singh, Anamika (National Geographical Journal of India, 2022)
Rainfall is the main source of water supply on the earth surface and it determines the moisture level at various depths of soil available to crops. The availability of moisture in soil is a controlling factor for growth and development of all types of vegetation especially for existing crops in an area. Day to day human activities are normally governed by the prevailing climatic conditions of a region while on the other hand climate itself is modified by different socio-economic activities of human beings like deforestation, farming practices, industrialization, rapid urbanization etc. The location and physiographic factors also combinedly influence the climatic characteristics of a region. In the same way climate helps to define climax vegetation of a region and also sets limits for crop growth. In this context, the numerical estimate of climatic water balance and its study has obtained an important place in geography In the present study an attempt has been made to describe the climatic characteristics of Varanasi and to evaluate the water balance parameters for Varanasi according to the revised scheme of Thornthwaite and Mather (1955).